Robotik, Navigation, Telechirurgie: Stand der Technik und Marktübersicht = Robots, Navigation, Telesurgery : State of the Art and Market Overview - Pott, Peter Paul; Schwarz, Markus (Zeitschrift für Orthopädie und ihre Grenzgebiete, 2002)
Currently surgical robots and navigation system are established in the OR. They assist the surgeon as active or passive navigators for orientation on the patient and for insertion of implants. In future, telesurgery will shaft medical experience over great distances. Aim: The goal of this paper is to describe applicable technologies, to analyse today’s state of the art and to list the available products in tables. Method: An extensive search in literature databases and company’s documents and personally conducted interviews were done for evaluation. Results: The systems can be categorized in “active” or “semi-active” (robots), “navigation systems” and “telesurgical workstations”. 14 robots, 22 navigation systems and four telesurgical workstations are described. Registration of anatomical structures can be performed with either pins, pair-point, surface, ultrasonic or fluoroscopic matching. At present optical, magnetic or mechanical localizer systems are used. Conclusion: The increased use of computer and image-guided methods (CAS and IGS) will optimize surgical treatment. The future has to show whether the necessary additional costs and time will bring better clinical results.
Gesehen am 14.01.2020